Legal Certainty of Homologation in Postponement of Debt Payment Obligations on The Fulfillment of Consumer Rights as Concurrent Creditors (Study: Cikarang District Court Decision No. 87/Pdt.G/2021/Pn Ckr) - Rizal, Sultan Ahmad; Sugiyono, Heru (Law Development Journal, 2025)
The legal instrument designed to shield financially distressed companies becomes a weapon that harms their consumers. This research illuminates this irony, demonstrating how a court-sanctioned debt restructuring agreement (homologation) under the Suspension of Debt Payment Obligations (PKPU) process, while ostensibly promising legal certainty, in practice strips property buyers of their rights. The Meikarta case vividly illustrates how easily consumers, despite significant financial investment, are relegated to the status of unsecured creditors with virtually nonexistent bargaining power. Where, then, does justice lie for them? This study seeks to answer this question by examining the tangible impacts of the homologation process and arguing that corporate accountability should not cease merely with a court decree. Moving beyond a textual analysis of statutes, this research delves into a pivotal decision by the Cikarang District Court (No. 87/Pdt.G/2021/PN Ckr) that dared to break from tradition. The findings are illuminating: while a homologation agreement is legally binding on all parties, a judge need not be a rigid "mouthpiece of the law" (bouche de la loi). Through legal discovery (rechtsvinding), a judge can progressively interpret rules to protect the vulnerable. The court's decision in this case to proceed with the consumer's lawsuit, notwithstanding the pre-existing PKPU decree, marks a crucial paradigm shift. It serves as a testament to the feasibility of achieving substantive justice, and this study dissects how such judicial courage can offer new hope for consumers entangled in complex legal disputes.